2021
DOI: 10.1007/s10690-021-09335-7
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investments, Renewable Electricity Output, and Ecological Footprints: Do Financial Globalization Facilitate Renewable Energy Transition and Environmental Welfare in Bangladesh?

Abstract: Phasing out fossil fuel dependency to adopt renewable energy technologies is pertinent for both ensuring energy security and for safeguarding the well-being of the environment. However, financial constraints often restrict the developing countries, in particular, from undergoing the renewable energy transition that is necessary for easing the environmental hardships. Against this background, this study makes a novel attempt to evaluate the impacts of FDI inflows on enhancing renewable energy use and attaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 149 publications
(174 reference statements)
2
25
0
Order By: Relevance
“…Danish et al ( 2019 ) concluded that accelerated adoption of renewable energy may help in the reduction of CO 2 emissions for Brazil, China, India, and Russia while investigating the existence of the EKC hypothesis for the period 1990–2015. Murshed et al ( 2021a , b ) evidenced the beneficial role of REC in the abatement of carbon emissions for five selected South Asian nations over 1995–2015.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Danish et al ( 2019 ) concluded that accelerated adoption of renewable energy may help in the reduction of CO 2 emissions for Brazil, China, India, and Russia while investigating the existence of the EKC hypothesis for the period 1990–2015. Murshed et al ( 2021a , b ) evidenced the beneficial role of REC in the abatement of carbon emissions for five selected South Asian nations over 1995–2015.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ARDL technique is favored over other existing co-integration techniques as it is best suited to smaller sample sizes, better accuracy, independent of the level of integration, and allows for investigation in different optimal lags compared to other conventional tests. Finally, following Murshed et al ( 2021a , b ), the ARDL technique can effectively address the potential endogeneity problems associated with some of the variables and offers unbiased estimates.…”
Section: Estimation Strategymentioning
confidence: 99%
“…For empirical analysis, we take the annual data of our concerned economies, i.e., Afghanistan, Iraq, Nigeria, Syria, Pakistan, Somalia, India, Yemen, Philippines, and Thailand from 1973 to 2016. Following Murshed et al (2021aMurshed et al ( , 2021b and Murshed et al (2021e), all the data are transformed into the logarithmic form to lessen the magnitude of variation and hence skewness. The selection of this panel of economies is based on the reason that these are the most-impacted countries by terrorism.…”
Section: Datamentioning
confidence: 99%
“…FDI is the believed to be the FDI inflows foremost driver of economic development since it plays an essential role in transferring capital and technology to developing nations (Murshed et al 2021b). Furthermore, the FDI inflows help the host economy to reap benefits of the latest know-how, management, and communication systems whereby such spillovers enhance productivity and economies of scale within the host nation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since more developing countries are opting to join the BRI scheme, the energy consumption-induced environmental problems can be expected to escalate in the years to come. This is because the developing countries are predominantly fossil fuel-intensive whereby a lion's share of their respective electricity outputs from gas, coal, and furnace oils (Rehman et al 2019;Murshed and Tanha 2021;Murshed et al 2021a). Besides, it is believed that the developing countries, in quest of globalization, tend to prioritize attainment of economic growth at the cost of environmental degradation (Murshed 2020a, b;Murshed et al 2021bMurshed et al , 2021c.…”
Section: Introductionmentioning
confidence: 99%